STUDI SURVEI LATIHAN LADDER DRILL TERHADAP KEMAMPUAN MENGGIRING BOLA PADA PEMAIN EKSTRAKURIKULER FUTSAL DI MA AL-IBROHIMY - Mohammad Nor Abdul Azis; Haryo Mukti Widodo; Agus Himawan; Septyaningrum Putri Purwoto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the futsal ball dribbling ability after implementing ladder drill training on futsal extracurricular students at Ma Al-Ibrohimy. The method used in this research was a survey, with a sample of 19 futsal extracurricular students, using the Quota Sampling technique. The instrument of this research is a futsal ball dribbling test to measure dribbling ability. The results showed that the lowest dribbling score was 9 and the highest score was 16. The calculated average value (M) was 11.59 with a standard deviation of 2.209. The conclusion of this research shows that the survey results analyzed using SPSS have a good score distribution. By implementing the right treatment, it is possible that dribbling results will increase compared to the values ​​obtained during the survey.